PO 8190 Risk factors of severe hepatotoxicity among HIV-1 patients initiated on highly active antiretroviral therapy in the northwest region of cameroon. (24th April 2019) - Abongwa, Lem Edith; Kibera, Anthony N; Fokunang, Charles; Torimiro, Judith; Nshom, Emmanuel; Domkam, Irénée; Okemo, Paul
Abstract : Background: Hepatotoxicity due to highly active antiretroviral therapy (HAART) has gained prominent attention since it can be affected by many factors. The aim of this study was to determine the prevalence of hepatotoxicity and related risk factors of severe hepatotoxicity following HAART initiation. Methods: A total of 100 newly diagnosed HIV drug-naive patients within the age range of 18–61 years were recruited and followed up for 24 weeks and were placed on either Tenofovir (TDF)+Lamivudine (3TC)+Efavirenz (EFV) or Zidovudine (AZT) +Lamivudine + Nevirapine (NVP) or Zidovudine +Lamivudine + Efavirenz regimen. Sociodemographic data was obtained using pretested questionnaires. Venous blood samples were collected to measure aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), using colometric enzymatic reaction. Hepatotoxicity was classified based on age and sex. Data was analysed using SPSS. Results: The level of significance was set at 5%. A total of 37 (38%) and 49 (49%) patients presented with hepatotoxicity; 15% and 28% of these patients had severe hepatotoxicity at 4 and 24 weeks, respectively. Serum levels of all enzymes increased significantly (p<0.05) with increased treatment duration. Univariate analysis revealed that the risk factor of developing severe hepatotoxicity was significantly (p<0.05) greater in patients<30 years, males, low BMI, low monthly income earners and patient on AZT+3TC +NVP regimen. While multivariate analysis at p<0.09 showed that age <30 years, Low BMI, low monthly income, or the use of AZT+3TC +NVP regimen were independent risk factors. Conclusion: Low BMI, <30 years, low monthly income and the use of AZT+3TC+NVP regimen were identifiable risk factors for the development of severe hepatotoxicity. As such, these factors should be considered as important for strategy by clinicians to prevent hepatotoxicity.